Genetic variation in ABCC4 and CFTR and acute pancreatitis during treatment of pediatric acute lymphoblastic leukemia - Bartram, Thies; Schütte, Peter; Möricke, Anja; Houlston, Richard; Ellinghaus, Eva; Zimmermann, Martin; Bergmann, Anke Katharina; Löscher, Britt-Sabina; Klein, Norman; Hinze, Laura; Junk, Stefanie V.; Forster, Michael; et al. (Journal of Clinical Medicine, 2021)
Background: Acute pancreatitis (AP) is a serious, mechanistically not entirely resolved side effect of L-asparaginase-containing treatment for acute lymphoblastic leukemia (ALL). To find new candidate variations for AP, we conducted a genome-wide association study (GWAS). Methods: In all, 1,004,623 single-nucleotide variants (SNVs) were analyzed in 51 pediatric ALL patients with AP (cases) and 1388 patients without AP (controls). Replication used independent patients. Results: The top-ranked SNV (rs4148513) was located within the ABCC4 gene (odds ratio (OR) 84.1; p = 1.04 × 10−14). Independent replication of our 20 top SNVs was not supportive of initial results, partly because rare variants were neither present in cases nor present in controls. However, results of combined analysis (GWAS and replication cohorts) remained significant (e.g., rs4148513; OR = 47.2; p = 7.31 × 10−9). Subsequently, we sequenced the entire ABCC4 gene and its close relative, the cystic fibrosis associated CFTR gene, a strong AP candidate gene, in 48 cases and 47 controls. Six AP-associated variants in ABCC4 and one variant in CFTR were detected. Replication confirmed the six ABCC4 variants but not the CFTR variant. Conclusions: Genetic variation within the ABCC4 gene was associated with AP during the treatment of ALL. No association of AP with CFTR was observed. Larger international studies are necessary to more conclusively assess the risk of rare clinical phenotypes.